The Jihad movements in the Sudanic belt : an analytical study of the Sokoto caliphate and the Sudanese Mahdiyyah - Idris, Adam Abba (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
At the beginning of the 19th century, a series of revolutionary Jihad movements emerged in the Sudanic Belt. However, those of Sheikh Usman Dan Fodio in the Hausaland and Muhammad Ahmad ibn Abdallah (popularly known as the Sudanese Mahdi) in the Nilotic Sudan were the most spectacular and successful of them all as they managed to uproot the regimes in their respective lands, and to replace them with militant Islamic states. After several years of teaching, preaching and fighting between these Jihadists and the rulers of their land, the military confrontation seemed to have been the only option left to the authorities to quell what they viewed as rebellions against them. From their own side, the Jihadist well understood this option and expected it, thus started preparing themselves for the eventual clash between them and their local authorities. This research aims to explore the motive behind these two major JihÉd movements as orchestrated by their leaders. It analyses their careers, thoughts and impacts in the region. The research also examines the notion of the Mahdiyyah in these movements vis-à-vis Islamic worldview. It pays special attention to the intellectual tussle between these Jihad leaders and the Ulama' of their time. Moreover, the study elaborately discusses their Jihad strategies, such as secret and public preaching, formation of supporters, Hijrah, Bay'ah, declaration of Jihad, Jihad tactics and the types of weapons they used in the battlefield. The research concludes by discussing the major legacies of these movements, in addition to presentation of major findings and recommendations for possible further research.